Rhetorical Invention in Design: Constructing a System and Spec. - Haller, Cynthia R. (Written Communication, 2000)
Presents a study which analyzed how one disciplinary design heuristic influenced the production of both a computer system and a specification text for the system. How textual content is rhetorically invented during design; Convergence of design and rhetorical invention; Discussion on information system cliche.